The Utilization of Virtual Reality in Destination Marketing in the Digital Era - Haryadi, Ahmad Fadli Putra; An, Sohyun; Chang, Kuang Yu (Tourism and Hospitality Research, 2026)
The rapid development of digital technology has significantly transformed destination marketing strategies in the tourism industry. Among emerging technologies, Virtual Reality (VR) has gained increasing attention due to its ability to deliver immersive, interactive, and emotionally engaging experiences for potential tourists. This study aims to examine the utilization of Virtual Reality in destination marketing within the digital era by synthesizing empirical findings from prior academic studies. Using a qualitative literature-based research design, this study systematically reviews and analyzes peer-reviewed journal articles and scholarly book chapters related to VR applications in tourism marketing. The analysis focuses on the role of VR in shaping destination image, enhancing tourist engagement, and influencing behavioral intentions. The findings indicate that VR contributes positively to destination marketing by strengthening emotional involvement, perceived presence, information quality, and visit intention. However, the effectiveness of VR varies depending on content design, level of interactivity, and user characteristics. The study concludes that Virtual Reality serves as a strategic marketing tool that complements traditional promotional methods rather than replacing them. This research provides theoretical contributions to digital destination marketing literature and offers practical insights for destination marketing organizations in adopting VR-based promotional strategies in the digital era.